AISI 4140 Steel Fatigue Performance: Cd Replacement by Electroplated Zn-Ni Alloy Coating - Ferreira Fernandes, Martin [UNESP]; dos Santos, Jefferson Rodrigo Marcelino [UNESP]; de Oliveira Velloso, Verônica Mara [UNESP]; Voorwald, Herman Jacobus Cornelis [UNESP] (Springer Nature, 2020)
The fatigue behavior of electrodeposited Zn-Ni alloy coating was investigated for its suitability to replace Cd coatings in AISI 4140 steel studs applied in oil and gas industries due to environmental and human health considerations. Axial fatigue tests were carried out at room temperature and statistically analyzed through two-parameter Weibull distribution. The coatings characterization included chemical composition and corrosion resistance analysis through energy-dispersive spectroscopy and salt spray tests, respectively. Furthermore, the fracture surfaces were observed using scanning electron microscopy, and the stress gradient in studs was obtained through finite element analysis. The experimental results showed that the notch sensibility was higher for high-cycle fatigue regime, varying from 0.20 to 0.61 for 104 and 105 cycles, respectively. The stress concentration effect influenced the fatigue life of the component, especially for low-stress levels, decreasing the fatigue strength in about 9% for 104 cycles and more than 20% for 105 cycles. The experimental fatigue data showed an increase in axial fatigue strength of about 8% for 105 cycles for electrodeposited Zn-Ni coating specimens, indicating feasibility with respect to fatigue behavior of the substitution of electrodeposited Cd for a Zn-Ni alloy.
Keywords: Cd coating; failure analysis; fatigue; finite element method; stress concentration; Zn-Ni coating